Molecular characterization and antagonism assesment of bacterial candidates as probiotics for fish aquaculture - Abdul Aziz, Mohamad Pipudin (2013)
The antagonistic ability of candidate probiotics Bacillus JAQ 04 and Micrococcus JAQ 07 towards selected fish pathogen Vibrio alginolyticus ATCC33839 were conducted in liquids modes via co-culture assay. Each probiotics were prepare in 3 different concentrations (102, 104 and 106 CFU ml-1) and each concentration inoculated with pathogen Vibrio alginolyticus 105 CFU ml-1 in liquid media of Tryptic Soy Broth to allow the antagonistic activity for 120 hours, the effectiveness of antagonistic will be measure by the reduction of V. alginolyticus colonies via plating count for each 24 hours interval for 120 hours. The observation of antagonistic effect of co-culture assays shows the reduction of V. alginolyticus colonies were reduced successfully by both probiotics strains compare to the control (V. alginolyticus 105 CFUml-1 alone). Bacillus strain JAQ 04 with high concentration (106CFUml-1) showed the effectiveness antagonism compare to Micrococcus strain JAQ 07. Bacillus strain JAQ 04 then assessed for molecular study. Studies in molecular level using PCR “Internal Transcribed Spacer (ITS)” is important to ensure that Bacillus strain JAQ 04 as a safety.